Impact of the South African Field Epidemiology Training Program, 2007–2018: A mixed-methods evaluation - Hetani Mdose; Mary Gaeddert; Carl Reddy; Natalie Mayet; Lazarus Kuonza (Journal of Interventional Epidemiology and Public Health, 2026)
Introduction: Since its inception, field epidemiology training programs (FETPs) have been strengthening the ability to prevent, detect, and respond to public health threats through workforce development across the world, hence strengthening global health security. The South African FETP (SAFETP) has enrolled a cohort of residents every year since 2007. This evaluation assessed the impact of SAFETP on increasing field epidemiology capacity in South Africa. Methods: We employed a mixed-methods approach and analysed both quantitative and qualitative data from multiple sources, including a descriptive analysis of SAFETP resident tracking data, a literature review of resident publications, key informant interviews with program stakeholders, and an online survey of graduates. Results: A total of 104 residents were enrolled in the past 11 SAFETP cohorts. There is a clear geographic clustering of activities and graduates in a few provinces, particularly Gauteng. The literature search revealed 149 articles with 49 residents as authors. Among the published papers directly related to training, 73% involved a resident as the first author, and 15% described an intervention that likely prevented illness. Informant interviews revealed themes related to the program’s impact on increased evidence-based decision-making and national epidemiological capacity and highlighted the need for a defined career path in epidemiology and increased visibility of the program. Conclusions: Noted impacts include providing trained graduates to the public health system, strengthening data-based decision-making, and disseminating results in scientific journals. The results confirm that FETPs can be effective at building epidemiologic capacity, but in-country institutional factors can limit their potential impact.